2002
DOI: 10.1034/j.1600-0749.2002.02052.x
|View full text |Cite
|
Sign up to set email alerts
|

Keratinocytes Control the Proliferation and Differentiation of Cultured Epidermal Melanocytes from Ultraviolet Radiation B‐Induced Pigmented Spots in the Dorsal Skin of Hairless Mice

Abstract: Long-term exposure of ultraviolet radiation B (UVB)-induced pigmented spots in the dorsal skin of hairless mice of Hos:(HR-1 X HR//De) F1. Previous study showed that the proliferative and differentiative activities of cultured epidermal melanoblasts/melanocytes from UVB-induced pigmented spots increased with the development of the pigmented spots. To determine whether the increase in the proliferative and differentiative activities of epidermal melanoblasts/melanocytes was brought about by direct changes in me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 42 publications
1
24
0
Order By: Relevance
“…We have shown that the proliferative activity of epidermal melanoblasts and melanocytes in serum-free primary culture [25,26] changes during the development of pigmented spots induced by UVB irradiation [27], and keratinocytes are involved in regulating this process [28][29][30]. However, little is known about the stages of differentiation of melanoblasts or melanocytes present in the pigmented spots.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that the proliferative activity of epidermal melanoblasts and melanocytes in serum-free primary culture [25,26] changes during the development of pigmented spots induced by UVB irradiation [27], and keratinocytes are involved in regulating this process [28][29][30]. However, little is known about the stages of differentiation of melanoblasts or melanocytes present in the pigmented spots.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the UV-induced epidermal hyperplasia, consisting of the hyperproliferative keratinocytes and melanocytes (Brenneisen et al, 2002;Chung, 2003;Hirobe et al, 2003) is considered to be due to the action of bFGF induced by UVB (Pittelkow and Shipley, 1989;Bielenberg et al, 1998). In Fig.…”
Section: Induction Of Nf-b and The Inhibitory Effects Of Parthenolidementioning
confidence: 99%
“…The UV-irradiated skin is characterized by fine and coarse wrinkling, roughness, dryness, laxity, and pigmentation (Chung, 2003). Microscopically, these changes can be explained by keratinocyte hyperproliferation and degradation of collagen fibers (Brenneisen et al, 2002), causing skin wrinkling and laxity, and melanocyte proliferation that leads to pigmentation characterized by dysregulation of melanocyte homeostasis and increase in the melanocyte density (Hirobe et al, 2003). The UV-induced production of proinflammatory cytokines, such as interleukin-1 (IL-1) and tumor necrosis factor ␣ (TNF␣), has been considered attributable to these changes (Corsini et al, 1997;Yarosh et al, 2000).…”
mentioning
confidence: 99%
“…3,34,35 The inhibitory effect of HSYA on UV-induced epidermal hyperproliferation was evaluated by directly measuring the thickness of epidermis. The results are shown in Fig.…”
Section: Hsya Inhibited Uv-induced Epidermal Hyperproliferationmentioning
confidence: 99%